Analysis of the Anthropometric Variables and their Relationship with the Pinch Force - Zea Forero, Christian Ricardo; Medina-Labrador, Manuel; Monroy Silva, Magda Viviana; Martinez Alvarez, Nardi Vanesa (Revista Mexicana de Ingenieria Biomedica, 2023)
The evaluation of the force in the hand is used in health and labor fields; it is composed of the grip force and the pinch force (Palmar Pinch - PP and Key Pinch - KP). The pinch force has not had significant amount of studies and connections with anthropometric variables. This work aimed to determine the relationship between the PP and KP strength with gender, dominance, age, and anthropometric variables. Using a Jamar dynamometer and with the participation of 681 subjects apparently healthy (48.9 % F and 51.1 % M) from the City of Bogotá (Colombia), who performed different occupational activities, it was found that the PP and KP forces were significantly higher in men than in women both in the non-dominant hand (8.27 Kgf Vs. 6.0 Kgf) and in the dominant hand (8.57 Kgf Vs 6.27 Kgf). The predictive models proposed in this study defined age, thickness, circumference, and maximum circumference of the hand as the main variables. In the female gender, age was established as the primary variable. At the same time, in the male, the circumference of the hand was defined in two models, and the maximum circumference of the hand in another two.